2020
DOI: 10.20409/berj.2019.219
|View full text |Cite
|
Sign up to set email alerts
|

Middle-Income Trap: The Case of Poland

Abstract: The middle-income trap (MIT) describes systemic growth obstacles shared by various countries that occur typically at the middle-income level of their development. The following analysis relies on Rostow's classification of the stages of economic development. We focus on Rostow stages three and four, where moving from labor intensive, import and foreign direct investment (FDI) driven growth to reliance on high value-added output and exports with embedded high content of capital and technology can render sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…To assess this vulnerability, we analyze changes in Poland's factor productivity, investment patterns, FDI, labor force educational attainments, new technology/product development, imports, export diversification, product complexity, and other factors. We conclude that certain conditions consistent with MIT are gaining importance in Poland and represent a challenge to its future economic growth (Leven, 2019). Aviliani, Siregar, & Hasanah (2014) used descriptive statistics in their paper titled "Addressing the middle-income Trap: Experience of Indonesia and found that more than 30 countries were in MIT.…”
Section: Literature Reviewmentioning
confidence: 88%
“…To assess this vulnerability, we analyze changes in Poland's factor productivity, investment patterns, FDI, labor force educational attainments, new technology/product development, imports, export diversification, product complexity, and other factors. We conclude that certain conditions consistent with MIT are gaining importance in Poland and represent a challenge to its future economic growth (Leven, 2019). Aviliani, Siregar, & Hasanah (2014) used descriptive statistics in their paper titled "Addressing the middle-income Trap: Experience of Indonesia and found that more than 30 countries were in MIT.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Az elmúlt egy évtizedben több kutató vizsgálta a közepes jövedelmi csapdát, és számos javaslatot fogalmaztak meg az okairól és megoldásáról. A csapda kialaku-lásának okai vita tárgyát képezik (Leven, 2019), és meglehetősen sokrétűek (Aiyar et al, 2013;Glawe & Wagner, 2016;WEF, 2016;Wang et al, 2018;World Bank, 2012). Az okok meghatározásához hasonlóan a közepes jövedelmi csapdából való kijutás módjában sincs egységes álláspont.…”
Section: Bevezetésunclassified
“…Az okok meghatározásához hasonlóan a közepes jövedelmi csapdából való kijutás módjában sincs egységes álláspont. Abban azonban általános az egyetértés, hogy egy bizonyos szintű fenntartható gazdasági növekedés szükséges hozzá (Acheampong & Udvari, 2020;Leven, 2019). A gazdasági növekedést nagyszámú hazai és nemzetközi tényező befolyásolja (Todaro & Smith, 2015).…”
Section: Bevezetésunclassified
“…However, Gill -Kharas (2015) posit that, although the endogenous growth theories and the Solow growth model were successful in addressing growth problems in high-income and low-income countries respectively, neither of those two frameworks was satisfactory in understanding and addressing the nature of economic growth challenges in middle-income countries; thus, the emergence of the MIT concept. This gave rise to the notion of MIT which is a relatively new phenomenon, conceptually (Glawe -Wagner, 2016;Leven, 2019).…”
Section: Concept Of Middle-income Countrymentioning
confidence: 99%